Correlative Multiscale 3D Imaging of a Hierarchical Nanoporous Gold Catalyst by Electron, Ion and X‐ray Nanotomography. Issue 13 (7th May 2018) - Fam, Yakub; Sheppard, Thomas L.; Diaz, Ana; Scherer, Torsten; Holler, Mirko; Wang, Wu; Wang, Di; Brenner, Patrice; Wittstock, Arne; Grunwaldt, Jan‐Dierk
Abstract: Tomographic imaging of catalysts allows non‐invasive investigation of structural features and chemical properties by combining large fields of view, high spatial resolution, and the ability to probe multiple length scales. Three complementary nanotomography techniques, (i) electron tomography, (ii) focused ion beam—scanning electron microscopy, and (iii) synchrotron ptychographic X‐ray computed tomography, were applied to render the 3D structure of monolithic nanoporous gold doped with ceria, a catalytically active material with hierarchical porosity on the nm and μm scale. The resulting tomograms were used to directly measure volume fraction, surface area and pore size distribution, together with 3D pore network mapping. Each technique is critically assessed in terms of approximate spatial resolution, field of view, sample preparation and data processing requirements. Ptychographic X‐ray computed tomography produced 3D electron density maps with isotropic spatial resolution of 23 nm, the highest so far demonstrated for a catalyst material, and is highlighted as an emerging method with excellent potential in the field of catalysis. Abstract : Exposed by tomography : Nanotomography offers a closer look at the inner workings of a catalyst, without damaging the structure. X‐rays, electrons and focused ion beam were used to map the 3D pore network of nanoporous Au on multiple length scales, allowing direct measurements of catalyst porosity, volume and surface area.